2016
DOI: 10.5812/hepatmon.36452
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and Risk Factors for Hepatitis B in an Adult Population: The First Report from Birjand, South Khorasan, Iran

Abstract: BackgroundInfection with the hepatitis B virus (HBV) is an important global health problem. Knowledge of the geographic distribution pattern of HBV infection can help to control the spread of the disease.ObjectivesTo determine the prevalence of HBV infections and risk factors for the disease for the first time in Birjand, Southeastern Iran.MethodsThis was an analytical cross-sectional study conducted in 2013 - 2014 of 5235 HBV cases in Birjand, South Khorasan Iran. Subjects aged 15 - 70 y were selected using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 16 publications
6
42
1
1
Order By: Relevance
“…There was no estimate of the national prevalence of HBV exposure, defined as positive HBV core antibody (antiHBc Ab), in Iran although several studies reported the prevalence at a city or province level (2)(3)(4)(5)(6)(7)(8)(9)(10). The prevalence of HBV infection, defined as positive HBV surface antigen (HBs Ag) in Iran was estimated as 1.7% in 1991 and 1999 (11), and 2.1% during 2001 -06 (12).…”
Section: Contextmentioning
confidence: 99%
“…There was no estimate of the national prevalence of HBV exposure, defined as positive HBV core antibody (antiHBc Ab), in Iran although several studies reported the prevalence at a city or province level (2)(3)(4)(5)(6)(7)(8)(9)(10). The prevalence of HBV infection, defined as positive HBV surface antigen (HBs Ag) in Iran was estimated as 1.7% in 1991 and 1999 (11), and 2.1% during 2001 -06 (12).…”
Section: Contextmentioning
confidence: 99%
“…The estimated population of Birjand is about 178 000. The city does not have many industries and is surrounded by deserts (19). Based on Sofian et al (18), the minimum sample size was determined by using the statistical formula of Fisher for calculating sample size (z 2 pq/d 2 ) Where; N = Minimum sample size for a statistically significant survey, Z = Normal deviant at the portion of 95% confidence interval = 1.96, P = prevalence value of total anti-HAV of 61% (P = 0.61), q = 1-p (q = 0.39), and d = margin of error acceptable or measure of precision = 0.05 as n=65.…”
Section: Methodsmentioning
confidence: 99%
“…The inclusion criteria were having the ability to respond to the interviewer, Iranian national identification card and age of 15 to 100 years. Further sampling details are presented by previous studies (12,13). After determination of the samples, study aims were explained and informed consent was obtained.…”
Section: Methodsmentioning
confidence: 99%